Estudo teórico do efeito do campo elétrico em nanotubos híbridos - Alves Junior, Elias Brito (2013)
This work studies through first-principles method based on Density Functional Theory (DFT) implemented by computer code SIESTA, the stability of the structures and electronic properties of hybrids nanotubes containing atoms of boron, carbon and the presence of nitrogen and an electric field. We analyze the values gap energy, formation energy and the variation of the total energy with respect to the nanotubes without application of field. For the electronic structure, there is the chart analysis of LDOS and band structure of these nanotubes as well as their polarizability.